Autoreb : robotization of the deburring of casting pieces - Araújo, Ricardo (2002)
In the industry of foundry, the deburring of casting pieces is an important stage. Since the piece presents edges in the junction zone of the casting moulds, those usually are not desirable and should be eliminated. For solving this problem it was idealized a robotic system capable of deburring casting pieces with minimum human intervention. Consists of an ABB robot, a table of coordinates for fixation and movement of the casting pieces, an artificial vision system for identification and quality control of the casting pieces, a Bosch high frequency straight grinder and an force sensor that closes the feedback loop of the deburring process control.